2002
DOI: 10.1046/j.1365-2567.2002.01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating immunoglobulin A‐ and immunoglobulin G‐secreting hybridoma cells in peripheral blood preferably migrate to female genital tracts. The role of sex hormones

Abstract: SUMMARYAntigen-specific circulating immunoglobulin-secreting cells (ISC) migrate to various secondary and tertiary lymphoid tissues. To understand the migration of the cells into the genital tract and its regulation by sex hormones, spleen-derived SG2 hybridoma cells secreting immunoglobulin G2b (IgG2b) and Peyer's patch-derived PA4 hybridoma cells secreting polymer IgA were labelled with 3 H-TdR, and intravenously injected into syngeneic mice of both sexes. Using flow cytometry, surface molecular markers of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Previous studies demonstrated that sex hormones regulate migration of circulating IgA ASCs into the genital tract (45). Moreover, both Igs and lactoferrin levels are suppressed in women given oral contraceptives (37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that sex hormones regulate migration of circulating IgA ASCs into the genital tract (45). Moreover, both Igs and lactoferrin levels are suppressed in women given oral contraceptives (37).…”
Section: Discussionmentioning
confidence: 99%